Designing a prototype planetarium typology with full dome imaging technology for enhancing and impactful cognitive experience / Mohd Aiman Yusuf, Kartini Kamsuri and Mohamed Tajulz Ariff - Yusuf, Mohd Aiman; Kamsuri, Kartini; Ariff, Mohamed Tajulz (College of Built Environment, 2023)
The new space economy in 2018 has been introduced to democratize the knowledge space related to economic fields, such as technology, engineering, education infrastructure and even tourism.